2016
DOI: 10.17261/pressacademia.2017.358
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between exchange rate and inflation: the case of Western Balkans Countries

Abstract: The paper investigates empirically the relationships between exchange rates and inflation in Western Balkan countries. The literature on the transition countries has recently focused on exchange rate as a shock absorber and downplayed its costs to macroeconomic stabilization. However, the decision to apply a different exchange rate regime depends on the costs and benefits in giving up an exchange rate instrument. With this in mind, the objective of this study is to determine whether fixed exchange rates play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
2
11
0
2
Order By: Relevance
“…Exchange rate in Pakistan has been rapidly depreciating rapidly that is causing inflation. This result is also consistent with economic theory as well as previous studies which concluded that the exchange rate has a significant effect on inflation, therefore any decision to change current monetary strategy i.e., applying fixed or flexible exchange rate must also take into consideration the associated costs and benefits (Fetai et al 2016).…”
Section: Model I Inflationsupporting
confidence: 91%
“…Exchange rate in Pakistan has been rapidly depreciating rapidly that is causing inflation. This result is also consistent with economic theory as well as previous studies which concluded that the exchange rate has a significant effect on inflation, therefore any decision to change current monetary strategy i.e., applying fixed or flexible exchange rate must also take into consideration the associated costs and benefits (Fetai et al 2016).…”
Section: Model I Inflationsupporting
confidence: 91%
“…Similarly, Joof and Jallow (2020) argued that a 1% increase in the inflation rate in the Gambia result from a 0.39% devaluation of domestic currency value against the US dollar. The works by Fetai, Koku, Caushi, and Fetai (2016) have found that the exchange rate volatility is the supreme cause of generating inflationary pressure in Western Balkan countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Implikasi dari rezim ini adalah tingkat kerentanan terhadap guncangan ekonomi yang begitu tinggi karena kredibilitas bank sentral yang relatif rendah. Koku et al, (2016)menguji pengaruh volatilitas nilai tukar terhadap inflasi di negara-negara Balkan barat seperti Albania, Serbia, dan Macedonia. Pengujian tersebut membuktikan bahwa nilai tukar memiliki pengaruh negatif yang sangat signifikan terhadap stabilitas harga di negara-negara tersebut.…”
Section: Inflation Targeting Framework (Itf)unclassified